Novel Semisynthetic Derivatives of Bile Acids as Effective Tyrosyl-DNA Phosphodiesterase 1 Inhibitors - Salomatina, Oksana; Popadyuk, Irina; Zakharenko, Alexandra; Zakharova, Olga; Fadeev, Dmitriy; Komarova, Nina; Reynisson, Jóhannes; Arabshahi, H.; Chand, Raina; Volcho, Konstantin; Salakhutdinov, Nariman; Lavrik, Olga (Molecules (Basel, Switzerland), 2018)
An Important task in the treatment of oncological and neurodegenerative diseases is the search for new inhibitors of DNA repair system enzymes. Tyrosyl-DNA phosphodiesterase 1 (Tdp1) is one of the DNA repair system enzymes involved in the removal of DNA damages caused by topoisomerase I inhibitors. Thus, reducing the activity of Tdp1 can increase the effectiveness of currently used anticancer drugs. We describe here a new class of semisynthetic small molecule Tdp1 inhibitors based on the bile acid scaffold that were originally identified by virtual screening. The influence of functional groups of bile acids (hydroxy and acetoxy groups in the steroid framework and amide fragment in the side chain) on inhibitory activity was investigated. In vitro studies demonstrate the ability of the semisynthetic derivatives to effectively inhibit Tdp1 with IC50 up to 0.29 µM. Furthermore, an excellent fit is realized for the ligands when docked into the active site of the Tdp1 enzyme.